A biometrics‐based anonymous authentication and key agreement scheme for wireless sensor networks. (2nd August 2021) - Fan, Qing; Chen, Jianhua; Xu, Feng; Li, Li; Luo, Min
Summary: Wireless sensor networks (WSNs) are widespreadly applicable for information acquisition and processing in various fields such as military, healthcare, envrionment monitoring, and so on. WSNs have three main components: sensors, gateways, and users. The sensing information from sensors is transmitted to users through gateways. However, the public wireless networks are vulnerable to malicious active and passive attacks, which could bring security and privacy issues. Numerous two‐factor based authentication and key agreement (AKA) protocols have been proposed to solve these issues, whereas these schemes still have some deficiencies. Three‐factor based authentication method can make up for the drawbacks of two‐factor based schemes. Kumari and Renuka put forward a biometrics‐based AKA for WSNs with elliptic curve cryptography (ECC). But their scheme cannot maintain anonymity and resist to impersonality attack, replay attack, and DoS attack. In this article, we propose a biometrics‐based anonymous AKA scheme, which is equipped with the covered security requirements of WSNs. Meanwhile, the proposed scheme are provably secure in the three‐party AKA security model. Performance analysis demonstrates that our scheme has better security properties, communication cost, and computational cost compared with five recent and related schemes.